Identification of suitable areas and effect of climate change on ginger - a GIS study. - A K Johny, V A Parthasarathy, Utpala Parthasarathy, K Jayarajan, (Journal of Spices and Aromatic Crops, 2008)
Secondary data of area, production and productivity of ginger have consistently shown aincreasing trend during the last 3 decades. Increase in area is not always in proportion withe increase in production. Thirty years area and production curves of the important ginggrowing states are compared with the Eco-crop suitability model which indicated thsuitability has direct impact on production. Orissa, West Bengal, Mizoram and Kerala avery highly suitable while North western states like Gujarat, Rajasthan, UttarpradesMadhya Pradesh are marginally suitable or unsuitable. North eastern and south westestates are ideally highly suitable for ginger cultivation. Future prediction of Eco-crop modshows, if the temperature increase by 1.5 to 2ºC, the suitability of Orissa and West Bengwill reduce drastically from high suitability to marginally suitable, indicating the effect climate change.